Integrating Islamic Economic Values into Climate Change Mitigation Policies for Sustainable Global Development - Lika Akana Helmi; Dedi Arianto; Mary Jane P. Rodriguez (Green Economics: International Journal of Islamic and Economic Education, 2024)
Climate change represents one of the most critical challenges of the 21st century, demanding immediate and coordinated global action. While various mitigation policies have been developed, including cap-and-trade schemes and carbon taxes, they often fail to fully address ethical concerns, such as equity, justice, and responsibility. This study explores the potential role of Islamic economic principles in strengthening climate change mitigation policies. Islamic economics, grounded in values like justice (Adl), stewardship (Khilafah), and communal responsibility, offers a moral framework that can enhance global efforts to combat climate change. Through a policy review and comparative analysis, the study examines the alignment of Islamic economic values with existing secular climate policies, highlighting their ability to address social and environmental injustices that often arise from traditional approaches. Additionally, the study discusses the practical applications of Islamic finance instruments such as Green Sukuk, Zakat, and Waqf, demonstrating their potential to fund sustainable projects. The integration of these Islamic values into international climate frameworks is shown to offer ethical and inclusive solutions, promoting a more just distribution of the burdens and benefits of climate action. This paper concludes by recommending that Sharia-based frameworks be incorporated into global climate policies and highlights the importance of future research in understanding the role of religious ethics in climate change mitigation.